Comunicación alternativa. Una lectura a la cultura hiphop en Medellín (2006)
This article has been written thanks to the confluence of vital experiences and knowhow’s that grouped their thoughts and explorations in order to set them into collective questioning and reconstruction. Behind this encounter lies an interdisciplinary perspective that attempts to bring forth a common ground to some concepts elaborated within Anthropology, Social work, Communication, Esthetics, and Research processes.The text is an outcome of the research: Musical Juvenile Mediations, developed in the Faculty of Communication of the University of Medellin (Colombia) and directed by Angela Garcés Montoya who, assisted in this research by Andrés Lopez, dialogues with Medina OXOC: a Rap singer, a Social-work student in the University of Antioquia, and an active teacher in the School of Juvenile Animation.